Clinical Comparison of New Peritoneal Suture and Traditional Suture in Transabdominal Preperitoneal Prosthetic Operation for Inguinal Hernia - Qin, Qiu Jian; Li, Hong Xue; Qin, Zhong Hui; Luo, Si Wen; Zheng, Hang; Huang, Shang Hui; Liao, Yu Ting; Zhu, Wen Liang (The Surgery Journal, 2025)
This study aimed to assess the efficacy of intraperitoneal suturing for peritoneal closure in preventing adhesions and improving clinical outcomes during laparoscopic transabdominal preperitoneal prosthetic (TAPP) hernia repair for inguinal hernia.A retrospective cohort study of 126 patients undergoing TAPP herniorrhaphy between November 2021 and November 2022 compared intraperitoneal suture technique (n = 64) versus conventional suturing (n = 62) for peritoneal flap closure. Evaluated parameters included demographic characteristics (age, sex, body mass index [BMI]), operative metrics (suture count, peritoneal closure time), procedural efficacy (complete peritoneal closure rate), and postoperative outcomes encompassing Visual Analog Scale (VAS) pain scores, adhesion formation, seroma incidence, recurrence rates, and intestinal obstruction occurrence.The intraperitoneal suture group achieved significantly higher complete internal inversion success rates (57 [89.1%] vs. 5 [8.1%]; p < 0.001), lower peritoneal adhesion incidence (1 [1.6%] vs. 9 [14.5%]; p = 0.018), and shorter peritoneal suture time (481.20 ± 47.91 vs. 584.77 ± 70.77 minutes; p < 0.001) compared with the traditional suture group. No significant intergroup differences were identified in age, sex, BMI, stitch counts, VAS scores, seroma, recurrence rates, or ileus incidence.The application of the intraperitoneal suture technique in TAPP to prevent peritoneal adhesion is effective, safe, and easy to learn, with good clinical effect and deserves promotion and application.
Keywords: laparoscope; peritoneal suture; TAPP; peritoneal adhesion